Single‐cell transcriptomic analysis of glioblastoma reveals pericytes contributing to the blood–brain–tumor barrier and tumor progression - Yuzhe Li; Changwu Wu; Xinmiao Long; Xiangyu Wang; Wei Gao; Kun Deng; Bo Xie; Sen Zhang; Minghua Wu; Qing Liu (MedComm)
Abstract The blood–brain barrier is often altered in glioblastoma (GBM) creating a blood–brain–tumor barrier (BBTB) composed of pericytes. The BBTB affects chemotherapy efficacy. However, the expression signatures of BBTB‐associated pericytes remain unclear. We aimed to identify BBTB‐associated pericytes in single‐cell RNA sequencing data of GBM using pericyte markers, a normal brain pericyte expression signature, and functional enrichment. We identified parathyroid hormone receptor‐1 (PTH1R) as a potential marker of pericytes associated with BBTB function. These pericytes interact with other cells in GBM mainly through extracellular matrix–integrin signaling pathways. Compared with normal pericytes, pericytes in GBM exhibited upregulation of several ECM genes (including collagen IV and FN1), and high expression levels of these genes were associated with a poor prognosis. Cell line experiments showed that PTH1R knockdown in pericytes increased collagen IV and FN1 expression levels. In mice models, the expression levels of PTH1R, collagen IV, and FN1 were consistent with these trends. Evans Blue leakage and IgG detection in the brain tissue suggested a negative correlation between PTH1R expression levels and blood–brain barrier function. Further, a risk model based on differentially expressed genes in PTH1R+ pericytes had predictive value for GBM, as validated using independent and in‐house cohorts.